Soil Carbon Characteristics of a Fluvisol Affected by Aggregates from Two Tillage and Crop Regimes - Emmanuel Onweremadu; Frank Akamigbo; Chigozie Asiabaka (Journal of Applied Sciences and Environmental Management)
We investigated soil carbon characteristics of a Fluvisol as influenced by different ped sizes and crop types for a period of 10 years in Owerri, Southeastern Nigeria. The experimental design was a split-split plot arranged in a randomized complete block design, with tillage technique serving as main plot; crop regime was the split plot and NPK fertilizer as split – split plot. Tillage techniques used were conventional tillage (CT) and minimum tillage (MT) while maize and soybean were used as crop types. Soil samples were collected at 20 cm depth with soil auger while core samples with cores partitioned 0 – to 10 – and 10 – to – 20 cm depth intervals were used to obtain soil samples for bulk density determinations. Routine laboratory analysis were conducted on soil samples and obtained data on crop and soil were statistically analyzed using analysis of variance (ANOVA) and means were separated using least significant differences (LSD) at P < 0.05. Aggregate size distribution was significantly (P < 0.05) influenced by tillage and crop type at 0 – 10 cm depth and soil carbon varied significantly (P < 0.05) with aggregate–size forms, tillage technique and crop species. Prediction of carbon behaviour in floodplain soils should take into consideration variability in ped forms, tillage method and crop types.